Aufstieg und Niedergang der Ricardianischen Wirtschaftstheorie - Fritz Rahmeyer (Universität Augsburg, Institut für Volkswirtschaftslehre, 2009)
After showing different criteria for assessing economic theories and in general terms the growth of (economic) knowledge, the essentials of classical British economic theory (Political Economy) are outlined. Next the scientific career and the genesis of the works of Ricardo are dealt with. The building blocks of his theory are Malthus' law of population and his own theory of land rent. They serve as a basis for developing his original theory of income distribution among the three classes of society (landowners, tenants, agricultural workers). His vision is - like that of Adam Smith - a self-adjusting model of the economy. Getting at first rid of rent, his intention was to show that - in contrast to Smith - a decrease of profits is the result of an increase in wages. Rent is a price determined, but not a price determining factor. The decline of profits reduces capital accumulation and economic growth and ends up in a stationary state of the economy. The precondition of his analysis of income distribution was a theory of value. Ricardo selected the quantity of embodied labour as an invariable measure of value. From a political point of view Ricardo opposed state interventions, such as the corn laws and the poor laws. He had trust in a self-regulating economy, unlike his friend and critic Thomas Malthus.
urn:nbn:de:bvb:384-opus4-711281
Keywords: B12; B31; D33; 330